LPS-Induced Inflammation Potentiates the IL-1β-Mediated Reduction of LH Secretion from the Anterior Pituitary Explants. (17th July 2013) - Herman, Andrzej Przemysław; Krawczyńska, Agata; Bochenek, Joanna; Dobek, Elżbieta; Herman, Anna; Tomaszewska-Zaremba, Dorota
Abstract : Acting at the level of the brain, interleukin- (IL-)1 β is considered to be one of the most potent downregulators of reproduction processes during immune/inflammatory challenge. IL-1 β suppresses gonadotropin-releasing hormone (GnRH) secretion from the hypothalamus resulting in the inhibition of the luteinizing hormone (LH) release from the anterior pituitary (AP). However, the presence of IL-1 β receptors in the AP suggests the possible direct action of this cytokine on LH secretion. The study was designed to determine the effect of IL-1 β on the LH secretion from the AP explants collected from saline and LPS-treated ewes in the follicular phase. It was found that IL-1 β suppressed (P ≤ 0.01 ) GnRH-stimulated LH release and LH β gene expression in AP explants in both groups. However, IL-1 β action was more potent in the explants collected from LPS-treated animals. Pituitaries from LPS-treated animals were characterized by increased (P ≤ 0.01 ) IL-1 type I receptor and decreased (P ≤ 0.01 ) GnRH receptor gene expression level compared to the saline-treated group. IL-1 β also affected the GnRH-R gene expression in explants collected from LPS-treated animals. Our results show that direct action of IL-1 β on the pituitary gonadotropes could be one of the reasons of the reproductive processes disorders accompanying an inflammatory state.